Aging and the Detection of Visual Errors in Scenes - Lori E. James; Toni M. Kooy (Journal of Aging Research)
Young and older adults performed a visual error detection task in two experiments. In Experiment 1, errors and anomalies were embedded in large, complex visual scenes, and participants were to find them and describe the nature of the identified problems. Young adults found more errors than older adults, a finding unrelated to age differences in near visual acuity or time constraints. Experiment 2 replicated the age difference in error detection using simplified visual scenes containing fewer errors. Results are interpreted as reflecting older adults' decreased ability to form representations for novel information, even though the task did not require the creation of new episodic memories.